Influence of Acid-Hydrolyzation of Juice of Cape Gooseberry (Physalis peruviana) Fruit on Solubility of Urinary Stones - Rani Sinha, Madhu; Dev, Avnisha; Prasad, Amita; Gosh, Mausumi; Tagore, R.N. (Asian Journal of Chemistry, 2011)
Urinary stones are the consequence of an alteration in the normal crystallization environment of urine in the urinary tract systems. Major factors responsible for crystal formation are supersaturation of Ca2+ salts and level of crystallization inhibitors (citrate and phytate). Increased citrate excretion decreases super saturation of calcium salt due to its capacity to make complex Ca2+ ions. Excessive citrate makes the urine more alkaline (pH between 6 and 7). This can be achieved by oral administration of alkalizer, citric fruits and its juices. The hardness of urinary stones varies from stone to stone, depending on size and their chemical compositions. The solubility of urinary stones of different forms (whole and powder) in natural-fresh juice and in acid-hydrolyzed juice of cape gooseberry (Physalis peruviana) fruit has been investigated and evaluated. The end result showed that solubility efficiency of natural fresh juice is higher than acid-hydrolyzed juice for urinary stones of different forms and sizes at all time intervals but more in beginning phase. Powder form of stone is more soluble than whole stone. Acid hydrolyzation augment litholysis activity only in initial phase, but later on, rather it increases the lithogenic effect. This short term study would be helpful in designing of natural (nonsynthetic and non-hydrolyzed) herbal formulation of cape gooseberry (Physalis peruviana) fruit juice for dissolving, at least partially 'the urinary stones'. However, additional studies are still needed to evaluate the role of juice of cape gooseberry (Physalis peruviana) fruit in long-term preventive and therapeutic management of urolithiasis.